Juridical Analysis of Criminal Sanctions for Money Laundering Proceeds of Narcotics Crimes - Pasaribu, Juhrin (Enigma Institute, 2024)
Money laundering proceeds of narcotics crimes is a criminal offense regulated in Law Number 8 of 2010 concerning prevention and eradication of the crime of money laundering. This crime is a serious crime that can endanger economic stability and state security. Criminal sanctions for laundering money from narcotics crimes are regulated in Article 3 of Law Number 8 of 2010. The criminal sanctions that can be imposed on perpetrators of this crime are in the form of a maximum imprisonment of 20 years and a maximum fine of IDR 10 billion. A juridical analysis of criminal sanctions for laundering money from narcotics crimes needs to be carried out to determine whether these sanctions are in accordance with the objectives of regulating this criminal act. The aim of regulating the crime of money laundering resulting from narcotics crimes is to prevent and eradicate the crime of money laundering, as well as to protect the interests of society and the national economy. Criminal sanctions for laundering money from narcotics crimes are in accordance with the objectives of regulating this crime. These criminal sanctions are preventive and repressive, so they can prevent and eradicate money laundering crimes, as well as provide a deterrent effect to perpetrators.